Challenges of the privatization process: The Case of TIBA Motors Corporation - Zandi Pour Joopari, GholamReza; Shahabi, Alireza; Naysary, Babak (Management Centre, IIUM, 2012)
This case study illustrates the issues regarding the initial public offer (IPO) of TIBA, an auto manufacturing company. Iran had recently initiated a privatization program. TIBA, the second leading company in the Iranian auto industry,was privatized in a vague and non-competitive manner. The directors of TIBA abused the Direct Benefits of Control (DBC) and exploited the existing information asymmetry in the market to take for themselves a massive block of TIBA shares through an investment company jointly set up by TIBA and a private sector company governed by TIBA directors. This IPO and the manner in which the investment companies were financed remain controversial. This study attempts to analyze this process and highlights its pitfalls.